Bre1 mediates the ubiquitination of histone H2B by regulating Lge1 stability. Issue 9 (24th April 2018) - Kim, Jueun; An, Yu‐Kyoung; Park, Shinae; Lee, Jung‐Shin
Abstract : Histone H2B ubiquitination mediated by the Rad6/Bre1 complex is crucial for regulating the stability and reassembly of the nucleosome. To understand the regulatory mechanisms of H2B ubiquitination, we explored proteins related to the Rad6/Bre1 complex. Interestingly, we observed that the stability of Lge1, reported to be a cofactor of Bre1, is greatly reduced in the absence of Bre1. The stability of Lge1 did require the middle fragment of Bre1 containing a coiled‐coil structure, but not its E3 ligase activity. Additionally, we found that Lge1 is involved in the 'writing' step of H2B ubiquitination. Our data suggest that Bre1 mediates H2B ubiquitination more precisely by maintaining the stability of Lge1 as well as through its role as a known E3 ligase. Abstract :